Cognitive superiority of Ukrainian stratcom as a meaningful interaction between internal and external narratives - Snytko , Olena (Current issues of Ukrainian linguistics: theory and practice, 2025)
The article is devoted to analysing the issue of cognitive superiority of Ukrainian strategic communications in situations of intense informational and psychological confrontation. The focus is on two contemporary Ukrainian narratives – ‘The Armed Forces of Ukraine as a factor in European security’ and ‘Ukrainians – destroyers of the Russian Empire’ – which have come to the fore in the contemporary information space. These narratives (external and internal) interact meaningfully within the Ukrainian strategic communications system, providing a cognitive advantage in communicating with target audiences and actively influencing the perception of events both within the country and on the international stage. These narratives have a solid foundation in real events, mobilising society to resist and maintaining a high level of responsibility in the face of life’s challenges, actively countering Russian propaganda narratives. The meaningful interaction of these narratives creates an image of Ukraine as a state fighting not only for its own freedom, but also for the freedom of all of Europe. The combination of the historical narrative and the narrative about the current threat makes it possible to assess the current Russian-Ukrainian war both as a continuation of centuries-old resistance and as a modern civilisational conflict: the Armed Forces of Ukraine are not simply holding back the aggressor, but are destroying the imperial structures that threaten the entire continent today. Interacting with each other, these narratives provide relevant semantic accents in Ukraine’s strategic communications. These narratives are being tested in the information space, demonstrating how the meaningful interaction of narratives ensures the cognitive dominance of Ukrainian strategic communications.